Rare penetrating abdominal injury caused by falling from height: Miraculously good prognosis - Liu, Yanquan; Xu, Qinglin; Zhu, Hongquan; Wang, Jun; Zeng, Fanlin; Lin, Jie (Frontiers in Surgery, 2022)
Fall from height causing penetrating abdominal visceral injuries is rare condition leading to abdominal multiorgan damage. It carries high mortality. A case of construction site worker sustaining penetrating visceral injuries by falling from height leading to impalement of steal bar from anus presented to our hospital and managed by timely evacuation from site of accident to hospital, resuscitations, radiological investigations and multi-Disciplinary team management lead to successful outcome. Our protocol for such cases will be discussed with references.